2011
DOI: 10.1097/jcp.0b013e318222b5dd
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6 Polymorphisms Influence the Plasma Concentration and Clearance of the Methadone S-Enantiomer

Abstract: Methadone is a racemic compound composed of the R-form and S-form enantiomers. The drug is usually used in maintenance therapy for the heroin-addicted patients. In our previous study, we found that the cytochrome P-450 (CYP) isozyme 2B6 preferentially metabolizes the S-methadone enantiomer. We thus tested whether CYP2B6 gene polymorphisms had any influence on the concentration or clearance of methadone. Ten single nucleotide polymorphisms within this gene region were evaluated in 366 patients undergoing methad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…CYP2B6 inhibition by ticlopidine increased methadone enantiomers AUC and reduced methadone N-demethylation and clearance (Kharasch and Stubbert, 2013). Pharmacogenetic studies also evidence CYP2B6 involvement in methadone disposition, with CYP2B6*6/*6 homozygotes having higher dose-adjusted S-methadone plasma concentrations and/or lower dose requirements than heterozygotes or noncarriers (Crettol et al, 2006;Wang et al, 2011;Levran et al, 2013).…”
Section: Controlmentioning
confidence: 95%
“…CYP2B6 inhibition by ticlopidine increased methadone enantiomers AUC and reduced methadone N-demethylation and clearance (Kharasch and Stubbert, 2013). Pharmacogenetic studies also evidence CYP2B6 involvement in methadone disposition, with CYP2B6*6/*6 homozygotes having higher dose-adjusted S-methadone plasma concentrations and/or lower dose requirements than heterozygotes or noncarriers (Crettol et al, 2006;Wang et al, 2011;Levran et al, 2013).…”
Section: Controlmentioning
confidence: 95%
“…Clinical genetic association studies of methadone plasma concentrations are consistent with diminished methadone N-demethylation by CYP2B6.6 and liver microsomes from CYP2B6*6 carriers. In patients, methadone doses were lower (Hung et al, 2011;Levran et al, 2013), and doseadjusted steady-state S-methadone concentrations were greater (Crettol et al, 2005(Crettol et al, , 2006Eap et al, 2007;Wang et al, 2011) in CYP2B6*6 homozygotes compared with heterozygotes and noncarriers. While these observations suggested that CYP2B6 allelic variants might influence clinical methadone pharmacokinetics, only recently has this been confirmed.…”
Section: Downloaded Frommentioning
confidence: 99%
“…CYP2B6 polymorphisms may influence clinical methadone disposition. Gene-association studies suggested that the CYP2B6*6 polymorphism was associated with higher dose-adjusted steady-state plasma methadone concentrations (Crettol et al, 2005(Crettol et al, , 2006Eap et al, 2007;Wang et al, 2011) or use of lower methadone doses (Hung et al, 2011;Levran et al, 2013). Formal determination of methadone N-demethylation and clearance showed that both were greater and lesser than wild-types, respectively, in CYP2B6*4 and CYP2B6*6 carriers (Kharasch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, associations between CYP2B6*6 genotype and higher dose-adjusted steady-state plasma methadone concentrations (Crettol et al, 2005;Crettol et al, 2006;Eap et al, 2007;Wang et al, 2011), and a need for lower methadone doses (Hung et al, 2011;Levran et al, 2012) have also been reported.…”
Section: Introductionmentioning
confidence: 99%